Disulfide‐Containing Detergents (DCDs) for the Structural Biology of Membrane Proteins. Issue 50 (13th August 2019) - Xue, Dongxiang; Xu, Tiandan; Wang, Huixia; Wu, Meng; Yuan, Ya; Wang, Wei; Tan, Qiwen; Zhao, Fei; Zhou, Fang; Hu, Tao; Jiang, Zhongxing; Liu, Zhi‐Jie; et al.
Abstract: Disulfide‐containing detergents (DCDs) are introduced, which contain a disulfide bond in the hydrophobic tail. DCDs form smaller micelles than corresponding detergents with linear hydrocarbon chains, while providing good solubilization and reconstitution of membrane proteins. The use of this new class of detergents in structural biology is illustrated with solution NMR spectra of the human G protein‐coupled receptor A2A AR, which is an α‐helical protein, and the β‐barrel protein OmpX from E. coli . Abstract : Bending for better : Detergents with a bent disulfide hinge in their hydrophobic tail facilitate efficient membrane protein solubilization and stabilization in small micelles. This new set of detergents can be feasibly used in NMR studies on α‐helical and β‐barrel membrane proteins (see figure).